(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The Authors report the biology of the Oxycarenus lavaterae (F.), a phytophagous depending on arboreous plants for its development and for its hibemation at the adult stage and herbaceous plants for the feeding of the post embryonic stages; the insect can feed on fruit-trees too (peach and apricot). The species is bivoltine: the first generation ends between May and July; the second one between mid-August and September. Malvaceae species and stone fruits are among the most appetizing hosts. The tree species preferred by insect for hibemation in colonies and the ways of controlling infested crops are listed.